PENINGKATAN LAYANAN PENEMPATAN KERJA MELALUI CUSTOMER RELATIONSHIP MANAGEMENT DENGAN METODE PROTOTIPE SIRP - Rivanthio, Tubagus Riko; Azzahra, Nabila; Risman, Dede Munawar; Suhendar, Asep Dadan (LPPM Universitas Sangga Buana, 2024)
The development of information technology provides easy access to information to customers so that speed and accuracy in service are needed. therefore technology-based Customer Relationship Management (CRM) is needed as good customer governance. LP3I Polytechnic the vocational universities that collaborates with many local and national company industry partners who working to improve graduate job placement services and fulfillment of human resources for company relations partners. but the problem managing many customers of company relations partners and graduates, form of trust that has been carried out not supported by good information system. The purpose of this research is the design and implementation of CRM through the Company Relationship Information System (SiRP) to improve the job placement services of LP3I polytechnic graduate vocational college. CRM system design method uses the SiRP prototype method, this method uses modeling tool, namely the UML. Design and implementation the CRM website application of SiRP prototype model is carried out in 4 stage where the communication stage, the SiRP application designed with UML and this system designs a system model in form of activity diagrams, use case diagrams and sequence diagrams. next at the Quick Plan and Modeling Quick Design stage as implementation of the system is designed for making user interfaces. The next stage is Construction of Prototype and Deployment Delivery & Feedback, which is the final stage for coding thoroughly and testing as the final stage of this pressman prototype method. Black box testing results in 100% usable for each module.